Alcune aggiunte al corpus di repliche derivanti della Madone embrassée par l’Enfant di Rogier van der Weyden - Luigi Agus (Papireto)
This study examines a series of nine unpublished paintings, dating between the 16th and 18th centuries, whose iconography derives from a lost prototype by Rogier van der Weyden, documented only through a drawing released from his workshop. This is the Madone embrassée par l'Enfant whose replicas have been cataloged several times with more and more additions, until recently reaching over 200, also distinguished by the different iconological meanings they have assumed over time, while maintaining the same composition. The new replicas demonstrate even more the diffusion of the model, both half-figure and full-figure.